2017
DOI: 10.1074/jbc.m116.769745
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathway for phagocyte priming upon encounter with apoptotic cells

Abstract: The phagocytic elimination of cells undergoing apoptosis is an evolutionarily conserved innate immune mechanism for eliminating unnecessary cells. Previous studies showed an increase in the level of engulfment receptors in phagocytes after the phagocytosis of apoptotic cells, which leads to the enhancement of their phagocytic activity. However, precise mechanisms underlying this phenomenon require further clarification. We found that the pre-incubation of a phagocyte cell line with the fragments of apoptotic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 75 publications
1
23
0
Order By: Relevance
“…Thus, efferocytosis of dead or late apoptotic virus-infected cells will be able to inhibit production of such non-enveloped viruses. Indeed, efferocytosis has been shown to inhibit replication of a non-enveloped virus, Drosophila C, both in vitro and in vivo (Nainu et al, 2015; Nonaka et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, efferocytosis of dead or late apoptotic virus-infected cells will be able to inhibit production of such non-enveloped viruses. Indeed, efferocytosis has been shown to inhibit replication of a non-enveloped virus, Drosophila C, both in vitro and in vivo (Nainu et al, 2015; Nonaka et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Viral infection induces changes of cell surface molecules related to cell death, and macrophages can recognize these changes and engulf the affected cells. It has been reported that macrophages perform efferocytosis of cells infected with the influenza (Fujimoto et al, 2000; Hashimoto et al, 2007; Shiratsuchi et al, 2000; Watanabe et al, 2005, 2002, 2004; Mukherjee et al, 2017), papilloma (Hermetet et al, 2016), and Drosophila C viruses (Nainu et al, 2015; Nonaka et al, 2017), as well as Lymphocytic choriomeningitis virus (LCMV) (Alatery et al, 2010), and Human Immunodeficiency Virus Type 1 (HIV-1) (Akbar et al, 1994). …”
Section: Introductionmentioning
confidence: 99%
“…The mRNA levels of various antimicrobial peptides, the Toll pathway-induced attacin and diptericin as well as the Imd pathway-induced defensin, drosomycin, and metchnikowin (10), were determined, and we found that the mRNA levels of some antimicrobial peptides, such as diptericin and defensin, marginally increased in flies after feeding with PHA-L4 ( Figure 6A). We then similarly analyzed the mRNAs of Draper and integrin αPS3-βν, engulfment receptors that activate two partly overlapping signaling pathways for the induction of phagocytosis of apoptotic cells by Drosophila hemocytes (21). The data indicated a dramatic increase in the levels of the mRNAs of both Draper and integrin βν in flies after lectin feeding ( Figure 6B): signals derived from the mRNA of integrin αPS3 were not detected under the conditions adopted in this study (data not shown).…”
Section: Increases In the Level Of The Mrnas Of Immunityrelated Protementioning
confidence: 86%
“…57,58 Nonetheless, clearance of apoptotic cells is associated with increased expression of phagocytic receptors in a number of phagocytic cell types, including macrophages. 12,[59][60][61] Drosophila embryonic macrophages also undergo remarkable shifts in behavior over the fly life cycle, controlled in part by lipid hormone signalling. 62,63 However, the anti-inflammatory phenotype associated with acute induction of apoptosis would necessitate rapid reprogramming, unlikely for lipid hormone signalling, suggesting a more rapid mechanism, such as release of find-me cues.…”
Section: Alternatively Factors Released By 'Undead' Cells (Cells Indmentioning
confidence: 99%